Effects of the Mediterranean Lifestyle During the COVID-19 Lockdown in Spain: Preliminary Study - Zaragoza-Martí, Ana; Sánchez-SanSegundo, Miriam; Ferrer-Cascales, Rosario; Gabaldón-Bravo, Eva Maria; Laguna-Pérez, Ana; Rumbo-Rodríguez, Lorena (Frontiers in Nutrition, 2021)
WWe aim to assess the beneficial effects of the Mediterranean style-diet before and after the period of confinement due to COVID-19 in a sample of 51 older patients who were part of a clinical trial of the Instituto de Investigación sanitaria y Biomédica de Alicante (ISABIAL, CEIM). Participants were randomly assigned to two conditions: experimental versus a control group. A pre-test survey assessment was conducted before confinement, while a post-test survey was conducted after the confinement period. Adherence to Mediterranean Diet and nutritional status were evaluated through self-reported questionnaires. Individuals who initiated the Mediterranean Diet intervention program before confinement increased 3,5% their level of adherence to the Mediterranean Diet and maintained their nutritional status after the confinement. In the case of BMI, there no were statistically significant differences between groups before and after confinement. These results suggest that adherence to the Mediterranean Diet may play an important role in the establishment of appropriate dietary guidelines in confinement situations such as the COVID-19.